Analisis Perkembangan Kinerja Keuangan Badan Layanan Umum pada Rumah Sakit Bhayangkara Kendari - Agus Bandang; Fadhel Rifkiadli; Andi Kusumawati; Haerial Haerial; Mahfiza Mahfiza (Al-Buhuts, 2025)
This study aims to analyze the development of Bhayangkara Hospital Kendari’s financial performance after implementing the Public Service Agency Financial Management Pattern in 2020–2024. The analytical tool used is financial ratios based on PER-22/PB/2020. The research applies a comparative descriptive design with a quantitative approach at Bhayangkara Hospital Kendari. Results showed that financial performance fluctuated during the five-year period. The highest score was recorded in 2022, reaching 75.53, categorized as good with an A predicate, while the lowest score occurred in 2024 with 60.53, categorized as fair with a BBB predicate. In general, the performance from 2020 to 2022 ranged between 69.74 and 75.53, consistently included in the good category with an A predicate. However, in 2023 and 2024, the scores decreased to between 60.53 and 67.11, shifting to the FAIR category with a BBB predicate. Overall, the hospital’s financial performance remained stable in the first three years under the good category, but showed a declining trend in the last two years, reflected in its shift to the fair category.